Uma análise estatística dos fatores de evasão e permanência de estudantes de graduação presencial da UFES - Sales Junior, Jaime Souza (2013)
In recent years, Brazilian universities have undergone expansion programs that have increased the number of higher education institutions, the number of courses offered, and the number of vacancies offered. A consequence of this expansion was an increase in the number of undergraduate student dropouts. A ‘drop-out’ is a student who abandons a course before its completion. Between 2007 and 2012, In the Federal University from Espírito Santo, an increase in the number of dropouts was registered totaling 5,886. Of these, 503 were to other institutions of higher education and 121 were to other courses of the university itself. One of the objectives of this research was to find factors and motivations that influence students to quit their classes or the whole higher education system entirely. The research methodology was to compare, through contingency tables and a logistic regression model, the graduates and dropouts who entered via college entrance between 2006 and 2011 and dropped out or graduated between 2007 and the first semester of 2012. The results showed that several factors are statistically related to dropping out of courses, all of which exist prior to student admission and academic experience. In the case of the institution of higher education that was investigated, seven factors most clearly explained the quitters: (i) opting for the social and ethnic quota system, (ii) the region of origin (iii) means of communication used for information, (iv) participation in research projects, (v) reception of student care, (vi) engaging in internship and (vii) number of class failures. Based on the results, actions were proposed and, if implemented, could result in a reduction in the number of dropouts at the institution.